Education in Preschool Educational Organizations in the Process of Information Communication Technologies Pedagogical Characteristics of Use - Sultanova Shakhnoza Umarhanovna (Research Parks Publishers, 2021)
This article discusses the role and benefits of the use of information and communication technologies in the development of children's mental abilities, memory and attention in the process of naturalization of children in preschool education, preparation for school education.